Neutron diffraction studies of tetrachloride liquids. IV: The molecular beat effect for TiCl4; SiCl4 and Tic4; SnCl4 mixtures. - Granada, J. R. (1980)
Fil: Granada, J. R. Comisión Nacional de Energía Atómica; Argentina